Prediction of liver toxicity and mode of action using metabolomics in vitro in HepG2 cells - Ramirez, Tzutzuy; Strigun, Alexander; Verlohner, Andreas; Huener, Hans-Albrecht; Peter, Erik; Herold, Michael; Bordag, Natalie; Mellert, Werner; Walk, Tilmann; Spitzer, Michael; Hofmann, Thomas; Hartung, Thomas (My University, 2018)
Liver toxicity is a leading systemic toxicity of drugs and chemicals demanding more human-relevant, high throughput, cost effective in vitro solutions. In addition to contributing to animal welfare, in vitro techniques facilitate exploring and understanding the molecular mechanisms underlying toxicity. New 'omics technologies can provide comprehensive information on the toxicological mode of action of compounds, as well as quantitative information about the multi-parametric metabolic response of cellular systems in normal and patho-physiological conditions. Here, we combined mass-spectroscopy metabolomics with an in vitro liver toxicity model. Metabolite profiles of HepG2 cells treated with 35 test substances resulted in 1114 cell supernatants and 3556 intracellular samples analyzed by metabolomics. Control samples showed relative standard deviations of about 10-15%, while the technical replicates were at 5-10%. Importantly, this procedure revealed concentration-response effects and patterns of metabolome changes that are consistent for different liver toxicity mechanisms (liver enzyme induction/inhibition, liver toxicity and peroxisome proliferation). Our findings provide evidence that identifying organ toxicity can be achieved in a robust, reliable, human-relevant system, representing a non-animal alternative for systemic toxicology.
Keywords: Metabolomics; Liver toxicity; In vitro; HepG2 cells; 570